THE EFFECTIVENESS OF APPLYING CONSTRUCTIVE CONTROVERSY METHOD IN GAINING STUDENTâS CRITICAL THINKING FOR WRITING ARGUMENTATIVE ESSAY - Komara, Cahya; Sriyanto, Widi (Getsempena English Education Journal, 2018)
AbstractThis research examined the effectiveness of applying Constructive Controversy method in terms of gaining studentâs critical thinking, thus their argumentative writing become solid. By using quasi-experimental design, this research took 20 students as respondents from both two classes, V-A as experiment class and V-B as control class. The scores of pre-test and post-test gathered from both classes are tested first through pre-requisites analysis; Normality of Kolmogorov-Smirnov and Homogeneity of Fisher. Then, the result of t-test showed that the t-observed was 2.88, and t-table was 2.02 on level of significance 0.05 with degree of freedom (df = n + n â 2) was 38. Regarding to the calculation, to > tt which means Ho hypothesis is rejected meanwhile Hi hypothesis is accepted. Therefore, Constructive Controversy method is effective to help students in gaining their critical thinking known from their arguments when writing argumentative essay.Â Â Â Â Â Keywords: Writing, Argumentative Essay, Constructive Controversy, Critical Thinking